Is age an independent risk factor for perioperative mortality and morbidity after radical prostatectomy? Analysis of the American college of surgeons national surgical quality improvement program database. Issue 2 (2nd April 2020) - Merhe, Ali; Hout, Mohammad; Abou Heidar, Nassib; El-Asmar, Jose M.; Jaafar, Rola; Mailhac, Aurelie; Tamim, Hani; Nasr, Rami
ABSTRACT: Objectives: To assess the safety and surgical outcomes of radical prostatectomy (RP) when looking at age as an independent risk factor of perioperative mortality and morbidity. Patients and methods: A retrospective cohort study was performed using American College of Surgeons National Surgical Quality Improvement Program database. Patients who underwent a RP from 2008 to 2015 were identified. They were divided into three groups based on their age 15 group at the time of surgery. Patients' characteristics were compared across the three following age groups: 74 years. The correlation between the three different age groups and their respective 30-day postoperative mortality and morbidity were assessed using logistic regression. Unadjusted and adjusted odds ratios (ORs) were estimated. Results: A total of 43025 patients were identified, 81.7% were aged 74 years. Overall, 102 patients died in the 30-day postoperative period. Univariate and multivariate analysis showed a significant increase in the 30-day postoperative mortality from 0.1% to 0.4% to 1.3% in the three different age groups 74 years, respectively. In addition, there was a significant increase in postoperative complications in the group of patients aged >74 years. A higher risk of complications 25 related to cardiac (OR 2.18 in age group 70–74 vs OR 7.45 in age group >74 years), respiratory (OR 2.36 vs OR 5.91), neurological (OR 2.28 vs OR 3.44), wound infections (OR 1.49 vs OR 3.25), and sepsis (OR 1.54 vs OR 2.64) were seen with the youngest group taken as a reference. Conclusion: Age is an independent risk factor for perioperative mortality and morbidity after RP in elderly patients. Therefore, age should be considered in the decision making of therapeutic options for patients with prostate cancer. Abbreviations: BMI: body mass index; CNS: central nervous system; SIOG: International Society of Geriatric Oncology; SEER: Surveillance, Epidemiology, and End Results; ACS: American College of Surgeons; NSQIP: National Surgical Quality Improvement Program; OR: odds ratio